Wide awake : the forgotten force that elected Lincoln and spurred the Civil War - Grinspan, Jon (Bloomsbury Publishing, 2024)
"At the start of the 1860 presidential campaign, a handful of fired-up young Northerners appeared as bodyguards to defend anti-slavery stump speakers from frequent attacks. The group called themselves the Wide Awakes. Soon, hundreds of thousands of young White and Black men, and a number of women, were organizing boisterous, uniformed, torch-bearing brigades of their own. These Wide Awakes--mostly working-class Americans in their twenties--became one of the largest, most spectacular, and most influential political movements in our history. To some, it demonstrated the power of a rising majority to push back against slavery. To others, it looked like a paramilitary force training to invade the South. Within a year, the nation would be at war with itself, and many on both sides would point to the Wide Awakes as the mechanism that got them there."--